Space and energy proceedings of the XXVIth International Astronautical Congress, Lisbon, 21-27 September, 1975 - Napolitano, Luigi G. (Pergamon Press, 1977)
Space and Energy contains the proceedings of the 26th Congress of the International Astronautical Federation, held in Lisbon, Portugal, on September 21-27, 1975. The papers explore developments and trends of interest as well as research in space and energy. Topics covered range from engineering and life sciences to space systems, space technology, and communication satellites. This book is comprised of 16 chapters and begins with a discussion on the Earth as an open system and how to utilize solar energy. The next section is devoted to engineering and life sciences and includes chapters giving surveys and/or assessments of a number of basic topics in astrodynamics and bioastronautics. Propulsion system concepts for a single stage shuttle are also considered, along with the reliability of outer planet spacecraft and the contribution of biological satellites to space biology and medicine. Specific systems such as an experimental hybrid rocket are also described. The last part evaluates application satellites, with particular reference to communication and earth resource satellites. This monograph should be of interest to space scientists and engineers.--Provided by publisher.